ANALISIS HASIL PEMERIKSAAN SARS-CoV-2 METODE RT-PCR di LABORATORIUM DAN RUMAH SAKIT RUJUKAN PALEMBANG - Anton Syailendra; Dian Adhe Bianggo NauE; Muhammad Ihsan Tarmizi; Sagita Kesuma Dewi (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2022)
Background: The spread of Corona Virus Disease-19 (COVID-19) caused by the SARS-CoV-2 coronavirus in the world is increasing so rapidly leads to the World Health Organization (WHO) announced the condition as a pandemic. The recommended test for SARS-CoV-2 is real-time reverse-transcription polymerase chain reaction (PRC), a method with high sensitivity and specificity. The outcome of the assay is the cycle threshold (Ct) value of the sample compared with a reference Ct value. However, there has been no standardization to determine threshold (Cycle threshold), the cycle number at which the fluorescence generated within a reaction crosses the fluorescence threshold, a fluorescent signal significantly above the background fluorescence, on different hosts. Each manufacturer of this method's reagent kit may vary at the threshold value so that the interpretation becomes subjective only to the kit's used. By considering that not all SARS-CoV-2 testing laboratories use the same reagent kit, we would like to study the Ct value of SARS-CoV-2 assay Methods: This research is an analytical descriptive study with a secondary data analysis approach. The data collected was the Cycle threshold (Ct) value of SARS-CoV-2 assay with RT-PCR method from Health Laboratory Center of Palembang (BBLK), PUSRI Hospital and Siti Fatimah Hospital. Results: during September-November 2020 there were 6,366 SARS-CoV-2 positive samples from 50,950 samples (12.49%); the RT-PCR type were multiplex techniques with two target genes, a combination of RdRP and N, RdRP and E, RdRP and ORF1ab. The average of Cycle threshold (Ct) value from positive test results for the target genes ORF1ab, RdRP, N and E were: 30.33; 28.44; 28.90 and 27.84 respectively . Keywords : Test result analysis, RT-PCR, SARS-CoV-2